Mitochondrial-Derived Peptide MOTS-c Increases Adipose Thermogenic Activation to Promote Cold Adaptation - Lu, Huanyu (Int J Mol Sci, 2019)
Cold exposure stress causes hypothermia, cognitive impairment, liver injury, and cardiovascular diseases, thereby increasing morbidity and mortality. Paradoxically, cold acclimation is believed to confer metabolic improvement to allow individuals to adapt to cold, harsh conditions and to protect them from cold stress-induced diseases. However, the therapeutic strategy to enhance cold acclimation remains less studied. Here, we demonstrate that the mitochondrial-derived peptide MOTS-c efficiently promotes cold adaptation. Following cold exposure, the improvement of adipose non-shivering thermogenesis facilitated cold adaptation. MOTS-c, a newly identified peptide, is secreted by mitochondria. In this study, we observed that the level of MOTS-c in serum decreased after cold stress. MOTS-c treatment enhanced cold tolerance and reduced lipid trafficking to the liver. In addition, MOTS-c dramatically upregulated brown adipose tissue (BAT) thermogenic gene expression and increased white fat “browning”. This effect might have been mediated by MOTS-c-activated phosphorylation of the ERK signaling pathway. The inhibition of ERK signaling disturbed the up-regulatory effect of MOTS-c on thermogenesis. In summary, our results indicate that MOTS-c treatment is a potential therapeutic strategy for defending against cold stress by increasing the adipose thermogenesis via the ERK pathway.